Beyond Corporate Social Responsibility: Corporate Sustainability-A Long Terin Perspective - Mehta, Jyotsna Diwan (Gyan Management Journal, 2009)
Issues of social responsibility and ethics are a perennial source of controversy. Several questions require to be answered: How important is it for organi
Keywords: Corporate Social Responsibility; Visible aspects; Integral aspects; Holistic View; Corporate Sustainability